Glycemic Control and Pregnancy Outcomes in Women with Type 2 Diabetes Treated with Oral Hypoglycemic Agents - Feghali, Maisa N.; Caritis, Steve N.; Catov, Janet M.; Scifres, Christina M. (American Journal of Perinatology, 2017)
Objective There is limited data regarding the use of oral hypoglycemic agents (OHAs) in pregnant women with type 2 diabetes mellitus (T2DM).Study Design This was a retrospective cohort study of women with T2DM who were treated with OHA or insulin from the first trimester onward. Bivariate and multivariate logistic regression analyses were used to compare pregnancy outcomes in women treated with OHA to those treated with insulin.Results One-third (67/198) of women were treated with OHA. Women treated with OHA had a shorter disease duration (4.4 vs. 6.8 years; p = 0.001), were more likely to have a normal prepregnancy body mass index, and had less gestational weight gain (GWG; 22.4 vs. 30.4 lbs; p = 0.005). A lower GWG was noted in obese women treated with OHA (19.9 ± 18.6 vs. 28.3 ± 17.7 pounds; p = 0.008). First-trimester hemoglobin A1c values were lower with OHAs, but second- and third-trimester values were similar. Among women who started pregnancy using OHA, 37/67 (55.2%) remained on OHA at delivery. Pregnancy outcomes did not differ between women who received OHA and those treated with insulin.Conclusion OHA treatment is more likely in women with T2DM who begin pregnancy with less severe disease, and use of OHA may be associated with decreased GWG.
Keywords: pregnancy; treatment; oral hypoglycemic agents; type 2 diabetes mellitus